2019
DOI: 10.1016/j.neuroimage.2019.04.059
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of automatic imitation: A meta-analysis and synthesis of fMRI studies

Abstract: complex organisational structures of control, which may involve contributions from multiple cognitive systems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 92 publications
3
37
0
Order By: Relevance
“…Methodological limitations of earlier studies called into question whether social cues thought to regulate automatic imitation could be actually affecting more domain-general mechanisms of response inhibition, such as spatial compatibility 18 . In line with this idea, a recent meta-analysis of neuroimaging studies found consistent evidence for the involvement of domain-general brain networks (e.g., dorsolateral frontoparietal cortex) in the control of imitative responses, and only limited support for the engagement of domain-specific systems related to social cognition, such as the theory of mind network 48 .…”
Section: Discussionmentioning
confidence: 97%
“…Methodological limitations of earlier studies called into question whether social cues thought to regulate automatic imitation could be actually affecting more domain-general mechanisms of response inhibition, such as spatial compatibility 18 . In line with this idea, a recent meta-analysis of neuroimaging studies found consistent evidence for the involvement of domain-general brain networks (e.g., dorsolateral frontoparietal cortex) in the control of imitative responses, and only limited support for the engagement of domain-specific systems related to social cognition, such as the theory of mind network 48 .…”
Section: Discussionmentioning
confidence: 97%
“…Initial neuroimaging experiment relying on such paradigms identified the anterior fronto-medial cortex (aFMC, Brass et al 2001;2005; and the TPJ (Brass et al 2005;Marsh, Bird & Catmur, 2016) as the brain substrate for the control of automatic imitative response tendencies. The brain network associated with the control of automatic imitation has however been questioned in a recent meta-analysis (Darda & Ramsey, 2019). These authors reported consistent evidence supporting that the control of automatic imitation is guided by brain regions associated with domain-general abilities allowing to deal with multiple demands (e.g.…”
Section: Self-other Distinction At the Action Levelmentioning
confidence: 99%
“…Moreover, if spatially distinct portions of temporoparietal junction show different effects that relate to social and attentional functions (Scholz, Triantafyllou, Whitfield-Gabrieli, Brown, & Saxe, 2009), then it seems even more important to functionally distinguish between these subdivisions when making specific claims about this area (Krall et al, 2015). Further, the largest fMRI work to date that used a multi-experiment, high-power approach (Darda, Butler, & Ramsey, 2018), as well as a meta-analysis of all related fMRI work (Darda & Ramsey, 2019), shows very limited evidence for specialised control processes in the context of imitation inhibition, but compelling evidence for generalised control. Such evidence contrasts with the initial fMRI research on imitation inhibition that used much smaller sample sizes, and argued for a socially-specific form of control in right temporoparietal junction (Brass et al, 2001;2003;Spengler et al, 2009).…”
Section: Compared Against Current Empirical Evidencementioning
confidence: 99%